2010
DOI: 10.1038/ejhg.2010.182
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of polymorphisms in genes related to sex hormones and abdominal aortic aneurysm

Abstract: Male gender and family history are risk factors for abdominal aortic aneurysm (AAA). We hypothesized that genes involved in sex hormones might be important in AAA. We investigated the association of aortic diameter with single-nucleotide polymorphisms (SNPs) in genes determining circulating sex hormones and their action. We genotyped 74 tagging SNPs across four genes (steroid 5a reductase, subfamily A, polypeptide 1 (SRD5A1), cytochrome P450, family 19, subfamily A, polypeptide 1 (CYP19A1), androgen receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…As genetic factors appear to have a role in the production, metabolism, and response to male sex hormones, an association was found between small AAAs and 1 SNP located in intron 1 of CYP19A1, but this finding was not confirmed in an independent cohort of large aneurysms. 27 As receptors of female sex hormones mediate their effects in vascular SMCs and in endothelial cells, genes encoding for these receptors provide biologically plausible candidate genes for genetic studies. A small study with 99 AAA cases and 225 controls revealed a polymorphism in the estrogen receptor b (ESR2) but not estrogen receptor a (ESR1), elastin (ELN ), progesterone receptor (PR), or transforming growth factor b1 (TGFB1) genes to be associated with AAA.…”
Section: Role Of Sex Hormones In Aaa Development and Growthmentioning
confidence: 99%
“…As genetic factors appear to have a role in the production, metabolism, and response to male sex hormones, an association was found between small AAAs and 1 SNP located in intron 1 of CYP19A1, but this finding was not confirmed in an independent cohort of large aneurysms. 27 As receptors of female sex hormones mediate their effects in vascular SMCs and in endothelial cells, genes encoding for these receptors provide biologically plausible candidate genes for genetic studies. A small study with 99 AAA cases and 225 controls revealed a polymorphism in the estrogen receptor b (ESR2) but not estrogen receptor a (ESR1), elastin (ELN ), progesterone receptor (PR), or transforming growth factor b1 (TGFB1) genes to be associated with AAA.…”
Section: Role Of Sex Hormones In Aaa Development and Growthmentioning
confidence: 99%
“…Some metabolic process-related genes, such as AHCY, CYP19A1, DNMT3A and EZH2, have been reported to participate in AAA. [31][32][33][34] For identified autophagy-related genes, MCL1, HIF1A, VEGFA, PARP1, AFT4 and CANX are essential for the survival and function of vascular cells and underlie AAA. 2,[35][36][37][38][39] Meanwhile, recent studies proved…”
mentioning
confidence: 99%
“…Some previously reported genes that influence AAA, such as Epidermal Growth Factor Receptor (EGFR) [ 42 ], Smad family member 1 (Smad1) [ 43 ], Estrogen Receptor (ESR2) [ 44 ], and STAT family member 3 (STAT3) [ 45 ], were successfully predicted by our level-2 PPI network, but not by the level-1 PPI network. These reported genes were not positive in our network because they were identified in animals, whereas only human genome-wide association study (GWAS) reports were used in the construction of our networks.…”
Section: Discussionmentioning
confidence: 96%